THE POLITICS OF THE CORPOREAL IN J.M. COETZEE’S WAITING FOR THE BARBARIANS (International Journal of Food and Nutritional Sciences, 2022)
Colonial incursion into different societies and cultures tends to marginalize and oppress the experiences and identity of the native population. The socio-political changes brought about by imperialism create an imbalance in power and representation between the colonizers and the natives. This paper attempts to study how the nuances of contact are problematized in the corporeal. The novel Waiting for the Barbarians written by J.M. Coetzee penetratingly studies how the subjugation of natives through violence and force manifests in the corporeal, and how this in turn is an effective tool of socio-political control in a colonial set-up. It will also explore how dehumanizing the body is a method of cultural imperialism exercised by colonizers.